Analisis ANALISIS FOKUS BELAJAR SISWA PADA MATA PELAJARAN MATEMATIKA DI KELAS 1 SD NEGERI REJODADI - Anjarwati, Nely; Purnomo, Heru (Widya Pustaka : Jurnal Ilmiah Pendidikan, 2025)
The focus of learning of first grade elementary school students is a challenge in the learning process, especially in Mathematics subjects that require concentration and early understanding of concepts. This study aims to analyze the factors that influence the focus of learning of first grade elementary school students of Rejodadi. This study uses a descriptive qualitative method with data collection techniques through observation, interviews, questionnaires, and documentation. The results of the study indicate that the lack of focus on learning is caused by internal factors such as low self-confidence, unstable physical and emotional conditions, and low interest in learning. In addition, external factors such as environmental noise, monotonous learning methods, and student seating positions also affect learning concentration. Questionnaire data shows that interference from peers is a dominant factor. As many as 16 out of 24 students scored below the KKM in Mathematics. These results indicate that lack of focus has a direct impact on students' academic achievement. This study emphasizes the importance of the role of teachers in creating varied, interactive, and conducive learning to improve students' focus and learning outcomes, especially in Mathematics learning in early grades.